TANGGUNG JAWAB YURIDIS DAN PERMASALAHANNYA TERHADAP BARANG JAMINAN GADAI DI PT PEGADAIAN CABANG AIR PUTIH KOTA SAMARINDA - Mika, Silwanus (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTPawnship office is Body of Effort Publik Ownerworkships which is its nucleus core in service area channeling of credit to societyÂ  assist government in improving prosperity of societybespecially fot middle economic faction downwords.Mortage is matter of important between pawnship office with society in worse of the happening of agreement of both parties by that of sociey need right and obligations of pawnship office and also society which with mortage which in pawn.Giving knownledge to society how to finish the problem of related to mortage as according to existing order so that do not is wrong of thigh between society with PT Pegadaian offiice.Can give knowledge and knowledge good to society and also for the interested parties with mortage so that can become benefit as all.Its keyword : Knowledge about Law Mortage Pwan